Muscle Grafts with Doxorubicin Pretreatment Produce “Empty Tubes” in the Basal Laminae, Promote Contentious Maturation of the Regenerated Axons, and Bridge 20-mm Sciatic Nerve Defects in Rats - Takeuchi, Hisataka; Sakamoto, Akio; Ikeguchi, Ryosuke; Ohta, Souichi; Noguchi, Takashi; Ando, Maki; Yoshimoto, Koichi; Sakamoto, Daichi; Matsuda, Shuichi (Journal of Reconstructive Microsurgery, 2022)
Background We newly developed a muscle graft that employs a doxorubicin pretreatment technique. The aims of this study were to reveal the biological and morphological features of the muscle tissue in the second week (Study I), to reveal the regeneration outcomes of functional and kinematic assessments of longer-term follow-up (16 weeks, Study II), and to make assessments of the muscle graft with doxorubicin pretreatment in the critical-sized nerve defect model (20 mm, Study III).Methods A total of 26 adult rats were used in this study. Doxorubicin treatment was accomplished by immersion in a doxorubicin solution for 10 minutes followed by a rinsing procedure. The rats were divided into three groups: the muscle graft with and without doxorubicin pretreatment (M-graft-w-Dox and M-graft-w/o-Dox) groups and the autologous nerve graft (N-graft) group. Assays of apoptosis, immunofluorescent histochemistry including CD68 (macrophage marker), scanning electron microscopy (SEM), morphometrical studies of the regenerated axons, nerve conduction studies, and kinematic studies were performed.Results The M-graft-w-Dox group contained significantly larger numbers of apoptotic cells and CD68-positive cells. SEM revealed the existence of the basal lamina, so called “empty tubes,” in the M-graft-w-Dox group. Study II showed contentious maturation of the regenerated axons, especially in the compound muscle action potentials. Study III showed that even at 20 mm, the M-graft-w-Dox group promoted axonal regeneration and functional regeneration.Conclusion The M-graft-w-Dox group showed superior regeneration results, and this easy and short-term procedure can expand the muscle graft clinical indication for the treatment of peripheral nerve defects.
Keywords: muscle; doxorubicin; peripheral nerve